PENEGAKAN HUKUM TERHADAP PELANGGAR KENDARAAN SEPEDA MOTOR PEDAGANG RONGSOKAN BERMUATAN LEBIH DI JALAN WR SUPRATMAN DENPASAR - Divani , Ade Arya; Wijaya, I Made Hendra (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Transportation is a form of movement carried out by humans or goods from one place to another by using a vehicle driven by humans themselves or machines. Many problems occur in the field of road and goods transportation. One case of violations in road transportation, namely overloaded vehicles, also known as ODOL (over dimension overload), still occurs frequently on a national scale. There are many articles that regulate traffic and road transportation in Law Number 22 of 2009. One of the articles that is in the spotlight in the background of this research problem is Article 307 concerning violations of overloading public transportation, which reads: Any person who drives a motorized vehicle who does not comply with the provisions regarding loading procedures, carrying capacity, vehicle dimensions as referred to in Article 169 paragraph (1) shall be punished with imprisonment for a maximum of 2 (two) months or a maximum fine of Rp500,000.00 (five hundred thousand rupiah).